Rural water quality problem and role of NGO in Gujarat (Note) - Ray, C.N. (2002)
The problem of quality of available drinking water in the rural areas of Gujarat is a serious health hazard. The inhabitants of these areas have to face the scarcity of drinking water as well as its poor quality. Some NGOs have taken initiative in creating awareness against the presence of excessive flouride in the water and have mobilised self-help groups in installing water treatment plants. The article discusses the magnitude of problem of varius districts of Gujarat and highlights the half-heated efforts of the administration in keeping floride content of water within permissible limits. a detailed account of the low-cost technical experiment by MACT for providing treated water. - Reproduced.
Keywords: Note; Nongovernmental organizations - India - Gujarat; Water quality - India - Gujarat; Water quality